IMPACT OF INBOUND MARKETING STRATEGY ON ENHANCING CUSTOMER ENGAGEMENT WITH THE MEDIATION OF ELECTRONIC SERVICE QUALITY - Ahmed Mohammed Ibrahim; Prof. Dr Kadhim Ahmed Jawad; Prof. Dr Maha Arif Breesam (Galaxy International Interdisciplinary Research Journal, 2023)
The study aims to test the effect of inbound marketing strategy (content marketing, social media marketing, search engine optimization, and marketing automation) as an independent (predictor) variable on customer engagement dimensions (attention, interaction, enthusiasm, immersion, and Identification) as a dependent (response) variable. It also examines the mediating role of electronic service quality dimensions (system availability, privacy/security, responsiveness, efficiency, and fulfillment) in this relationship. The study is significant both theoretically and practically, as it can be employed to guide future orientations of businesses, whether large or small, in increasing sales, maximizing profits, and consequently expanding market share. The research problem is framed by several questions, the most important of which are: Does inbound marketing strategy enhance customer engagement? Does the impact of this strategy on customer engagement amplify through electronic service quality among Generation Z? To achieve the study’s objectives and answer its research questions, a descriptive-analytical approach was adopted, and an electronic questionnaire in the form of a Google form was used as the main data collection tool. The research targeted students from Mustansiriyah University belonging to Generation Z as the research population, with a sample size of 1170 randomly selected respondents. The study also aimed to test several main and sub hypotheses related to the relationships and effects, as well as the hypothesis of significant differences between males and females in terms of the study variables. The data analysis utilized SPSS V.28, AMOS V.26, and various statistical techniques such as mean, standard deviation, relative importance, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), simple linear regression, path analysis, and independent samples t-test. The study yielded a set of results, the most important of which indicate that the impact of inbound marketing strategy on customer engagement is amplified through electronic service quality. Based on the achieved results, several conclusions were drawn, including the importance of organizations providing high-quality electronic services to Generation Z customers in order to enhance the implementation of marketing strategies and strengthen customer engagement with the organization or its brand, making them less susceptible to the influence of competing organizations.